Prevalence of Tuberculosis Infection among Various Risk Groups in India: A Systematic Review and Meta-Analysis - Arohi Chauhan; Malik Parmar; Girish Dash; Hardik Solanki; Sandeep Chauhan; Krushna Chandra Sahoo; Bhavin Vadera; Raghuram Rao; Ravinder Kumar; Kiran Rade; Sanghamitra Pati (Wolters Kluwer Medknow Publications, 2024)
Treatment of tuberculosis (TB) infection (TBI) to prevent active TB disease is a key component of the National Strategic Plan to end TB in India, without which the strategies to end TB would be futile. There is a need to rapidly scale up access to effective shorter regimens for tuberculosis preventive treatment (TPT) to a wider set of risk groups. This applies for identifying high-risk groups for TPT expansion. Thus, our aim with this review is to determine the TBI prevalence in different risk groups in India. We searched databases like Embase, Medline, Scopus, and CINAHL for studies published between 2012 and 2023 to estimate TBI in different risk groups in India. The PRISMA guidelines were followed when reviewing the publications, and a predetermined search strategy was used to find relevant sources across various databases. Using MetaXL (MS excel) software, we pooled data based on a random-effects model, along with heterogeneity testing using Cochrane's Q and I2 statistic. A total of 68 studies were included from 10,521 records. TBI pooled prevalence was estimated using the IGRA data, while in the absence of IGRA data, TST data were utilized. The key findings revealed a total of 36% pooled TBI prevalence for all risk factors, 59% among smokers, 53% among diabetics and alcoholics, 48% among malnourished, 47% among contacts of TB patients, 44% among HIV, 36% among pregnant women, 35% among COVID-19 patients, 31% among healthcare workers, 18% among sarcoidosis patients, and 15% among rheumatoid arthritis patients in India. Our review depicted a high TBI burden among groups such as diabetes mellitus, smokers, malnourished, and alcoholics. WHO has yet to recommend for systematic screening and treatment for TBI among these groups for want of evidence which this study provides, highlighting the need to reprioritize the risk groups for tailored TPT strategies.